119k views
2 votes
Rearrange x=3g+2 to make g the suject

please explain this to me well

User Uomo
by
5.6k points

2 Answers

2 votes

Answer:

(x-2)/3 = g

Explanation:

First you move the 2 over to the same side as the x by subtracting it on both side, because you are trying to make the g "alone". Then you move the 3 by doing the inverse, just like with the 2. Since you are multiplying 3 on one side to move to the other side you have to divide both sides by 3.

User Chris Hannon
by
5.2k points
3 votes

Answer:

g= (x-2)/3

Explanation:

x=3g+2

Subtract 2 from each side

x-2=3g+2-2

x-2 = 3g

Divide each side by 3

(x-2)/3 = 3g/3

(x-2)/3 =g

g= (x-2)/3

User David Watson
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.